Reconstruction of diet of population from Roman period (1st-4th c. A.D.) on Pruszcz Gdański cemetery material - Gładykowska-Rzeczycka, Judyta Julia; Smrčka, Václav; Jambor, Jaroslav (Polskie Towarzystwo Antropologiczne, 1997)
The cemeteries of the Wielbark culture in Pruszcz Gdański date back to the beginning of our era. Their location near the Baltic Sea suggests some connection with Germanic tribes. In an attempt to reconstruct the diet of the buried there, 182 bone samples were taken from 48 skeletons there and subjected to analysis for chemical elements. The data show the bone samples had a zinc-dominant microelement composition that has been also observed at Germanic burial places situated along the frontier of the Roman Empire. Our supposition is that the diet of the population was dictated by their customs rather than by the natural environment conditions there.